2022
DOI: 10.3390/jfb13010015
|View full text |Cite
|
Sign up to set email alerts
|

Fixed Prosthetic Restorations and Periodontal Health: A Narrative Review

Abstract: Periodontal health plays an important role in the longevity of prosthodontic restorations. The issues of comparative assessment of prosthetic constructions are complicated and not fully understood. The aim of this article is to review and present the current knowledge regarding the various technical, clinical, and molecular aspects of different prosthetic biomaterials and highlight the interactions between periodontal health and prosthetic restorations. Articles on periodontal health and fixed dental prosthese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 130 publications
(180 reference statements)
0
56
0
Order By: Relevance
“…Intra-oral ceramic restorations are regularly exposed to acid-base changes and temperature fluctuations produced by food and drink consumption. Therefore, in ideal circumstances the dental ceramic restorations should resist or only have minimal changes in such environments [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intra-oral ceramic restorations are regularly exposed to acid-base changes and temperature fluctuations produced by food and drink consumption. Therefore, in ideal circumstances the dental ceramic restorations should resist or only have minimal changes in such environments [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The enlarged SEM images of the various zirconia subgroups revealed that subgroup 3 had cement degradation, which worsened with subgroup 4. This might lead to an increase in the microleakage percentages for the examined subgroup Figures (7)(8)(9)(10).…”
Section: Scanning Electron Microscopementioning
confidence: 99%
“…Improperly constructed "interim" restorations may cause periodontal inflammation and gingival recession and the requirements for fit, polish, and contour in the interim restoration should be the same as for the final restoration. Sometimes, inappropriate prosthetic treatment planning or the prosthesis itself can cause periodontitis or gingival recession [12].…”
Section: Introductionmentioning
confidence: 99%